2021
DOI: 10.1016/j.celrep.2021.108925
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 reduces C9orf72 HRE-induced neurotoxicity in the absence of nonsense-mediated decay dysfunction

Abstract: SUMMARY Multiple cellular pathways have been suggested to be altered by the C9orf72 GGGGCC (G 4 C 2 ) hexanucleotide repeat expansion (HRE), including aspects of RNA regulation such as nonsense-mediated decay (NMD). Here, we investigate the role that overexpression of UPF1, a protein involved in NMD, plays in mitigating neurotoxicity in multiple models of C9orf72 ALS/FTD. First, we show that NMD is not altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
(53 reference statements)
2
23
0
Order By: Relevance
“…Although this strongly refutes the presence of any NMD dysfunction in C9ALS, this study corroborates that UPF1 is neuroprotective in this context ( Zaepfel et al, 2021 ). Evidence is provided that UPF1 overexpression reduces the abundance of DPRs in multiple models, potentially explaining its neuroprotective effects ( Zaepfel et al, 2021 ). However, much is still left unanswered by these papers to precisely explain the role that UPF1 plays in supporting neuronal health.…”
Section: C9orf72supporting
confidence: 80%
See 4 more Smart Citations
“…Although this strongly refutes the presence of any NMD dysfunction in C9ALS, this study corroborates that UPF1 is neuroprotective in this context ( Zaepfel et al, 2021 ). Evidence is provided that UPF1 overexpression reduces the abundance of DPRs in multiple models, potentially explaining its neuroprotective effects ( Zaepfel et al, 2021 ). However, much is still left unanswered by these papers to precisely explain the role that UPF1 plays in supporting neuronal health.…”
Section: C9orf72supporting
confidence: 80%
“…Thus, it is difficult to conclude from these studies whether NMD function is at all altered by the HRE in human patients. A very new study has attempted to answer this question using an human induced pluripotent stem cell-derived spinal neuron (iPSN) model of C9ALS ( Zaepfel et al, 2021 ). Following validation of several bona fide transcripts as substrates for NMD, it was demonstrated that neither the steady-state abundance nor stability of these substrates is altered in C9ALS patient-derived iPSNs relative to age- and sex-matched controls ( Zaepfel et al, 2021 ).…”
Section: C9orf72mentioning
confidence: 99%
See 3 more Smart Citations